Upper crustal structure of NW Iran revealed by regional 3-D Pg velocity tomography. Issue 2 (14th May 2020) - Maheri-Peyrov, Mehdi; Ghods, Abdolreza; Donner, Stefanie; Akbarzadeh-Aghdam, Maryam; Sobouti, Farhad; Motaghi, Khalil; Hassanzadeh, Mirali; Mortezanejad, Gholamreza; Talebian, Morteza; Chen, Ling
SUMMARY: We present the result of a 3-D Pg tomography in NW Iran to better understand the relationship between seismicity and velocity structure within the young continental collision system. In this regard, we have collected 559 07 Pg traveltime readings from 3963 well located earthquakes recorded by 353 seismic stations including 121 stations from four new temporary seismic networks. The most prominent feature of our Pg velocity model is a high correlation between the location of majority of large magnitude events and the location of low velocity regions within the seismogenic layer. The large instrumental and historical earthquakes with some limited exceptions tends to happen close to the borders of the low velocity regions. The Lorestan arc of Zagros has the thickest (∼20 km) low velocity region and Central Iran has the thinnest (less than 10 km) low velocity region where little seismicity is observed. Despite the relative increase of thickness of low velocity region in the uppermost part of the upper crust of Alborz, the average Pg velocity of the upper crust increases from Central Iran towards Alborz and reaches to its climax in the northern hills of Alborz, where the catastrophic Rudbar-Tarom 1990 event happened. The Pg velocity map shows presence of a low angle basement ramp in the Lorestan arc at the depth range of ∼10–20 km. The large low angle thrust Ezgele-Sarpolzahab 2017 earthquake and medium size high angle thrust events happened at the base and updip part of the velocity ramp, respectively. The calculated Pg velocity map shows low velocity regions at depths deeper than 11 and 20 km beneath the Sahand and Sabalan volcanoes, respectively.